Education for democracy in England in World War II - Ku, Hsiao-Yuh, 1979- author.
1 online resource.
Keywords: "Education for Democracy in England in World War II examines the educational discourse and involvement in wartime educational reforms of five important figures, Fred Clarke, R. H. Tawney, Shena Simon, H. C. Dent, and Ernest Simon. These figures campaigned for educational reforms through their books, publishing articles in newspapers, delivering speeches at schools and conferences, and by organizing pressure groups. Going beyond the literature in this key period, the book focuses on exploring the relationship between democratic ideals and reform proposals in each figure's arguments. Displaying a variety of democratic forums for debates about education beyond parliament, the book re-interprets wartime educational reforms from a different perspective and illustrates the agreements and contradictions in the educational discourse itself"--